2021
DOI: 10.37689/acta-ape/2021ao01113
|View full text |Cite
|
Sign up to set email alerts
|

Impacto dos sintomas de ansiedade e depressão na autoeficácia percebida em estudantes de enfermagem

Abstract: Impacto dos sintomas de ansiedade e depressão na autoefi cácia percebida em estudantes de enfermagem Impact of anxiety and depression symptoms on perceived self-effi cacy in nursing students Impacto de los síntomas de ansiedad y depresión en la autoefi cacia percibida de estudiantes de enfermería

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
(36 reference statements)
0
2
0
6
Order By: Relevance
“…In the original version, T1 indicated that items 1, 2, 5, 7, 8, 15, 16, 18, 20, 27, 29 and 30 started with an unstressed oblique pronoun, however, as described by the Brazilian Academy of Languages, it is not recommended to start sentences with an unstressed oblique pronoun (me, se, te, a, o, lhe, nos, vos, as, os, lhes), the sentence should be started with the verb and, if feasible, the pronoun "se" should be placed afterwards (27) . In the USDI-BR version, all these items had the personal pronoun "eu" (I).…”
Section: Discussionmentioning
confidence: 99%
“…In the original version, T1 indicated that items 1, 2, 5, 7, 8, 15, 16, 18, 20, 27, 29 and 30 started with an unstressed oblique pronoun, however, as described by the Brazilian Academy of Languages, it is not recommended to start sentences with an unstressed oblique pronoun (me, se, te, a, o, lhe, nos, vos, as, os, lhes), the sentence should be started with the verb and, if feasible, the pronoun "se" should be placed afterwards (27) . In the USDI-BR version, all these items had the personal pronoun "eu" (I).…”
Section: Discussionmentioning
confidence: 99%
“…Na versão original, a T1 indicou que os itens 1, 2, 5, 7, 8, 15, 16, 18, 20, 27, 29 e 30 iniciavam com pronome oblíquo átono, porém, conforme descreve a Academia Brasileira de Letras, não é recomendado iniciar frases com pronome oblíquo átono (me, se, te, a, o, lhe, nos, vos, as, os, lhes), devendo-se começar a frase com o verbo e, se for viável, colocar o pronome "se" colocado na sequência (27) . Na versão USDI-BR, todos esses itens ficaram com pronome pessoal "eu".…”
Section: Discussionunclassified
“…Trata-se de uma revisão integrativa da literatura, realizada a partir das recomendações PRISMA 12 , que visou sintetiza resultados de estudos de maneira organizada 13 .…”
Section: Metodologiaunclassified